2017
DOI: 10.1177/1533034617733904
|View full text |Cite|
|
Sign up to set email alerts
|

Long Noncoding RNA H19 Inhibits Cell Viability, Migration, and Invasion Via Downregulation of IRS-1 in Thyroid Cancer Cells

Abstract: Thyroid cancer is a common endocrine gland malignancy which exhibited rapid increased incidence worldwide in recent decades. This study was aimed to investigate the role of long noncoding RNA H19 in thyroid cancer. Long noncoding RNA H19 was overexpressed or knockdown in thyroid cancer cells SW579 and TPC-1, and the expression of long noncoding RNA H19 was detected by real-time polymerase chain reaction. The cell viability, migration, and invasion were determined by 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 31 publications
2
44
1
Order By: Relevance
“…After 24 h, the invaded cells were fixed using 4% paraformaldehyde and were stained using 1% crystal violet. The number of invaded cells was counted (Wang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…After 24 h, the invaded cells were fixed using 4% paraformaldehyde and were stained using 1% crystal violet. The number of invaded cells was counted (Wang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…H19 mediated negative down regulation of insulin receptor by inactivation of PI3 kinase/Akt and nuclear factor Kappa B pathway. Owing to these characteristics, H19 may be potentially used as a therapeutic target for TC (Wang et al, 2017). Using qPCR, it was they demonstrated that downregulation of H19 was responsible of reduced metastatic potential in PTC and thus H19 expression could be utilized as diagnostic marker for PTC (Jiao et al, 2019).…”
Section: H19mentioning
confidence: 99%
“…Liang et al reported that H19 was overexpressed in papillary thyroid carcinoma (PTC), and H19 overexpression contributes to epithelial-mesenchymal transition (EMT) [18]. However, Wang et al reported that H19 overexpression inhibited invasion and EMT in PTC cells [19], and Lan et al reported that H19 downregulation contributes to proliferation and migration in PTC cells [20]. H19 expression and its role in ATC were still unclear.…”
Section: Introductionmentioning
confidence: 99%